People aretha franklin emagazine (PEOPLE Aretha Franklin.)
PEOPLE celebrates the peerless Aretha Franklin. In words and pictures, this special edition offers an in-depth look at Franklin’s career, from singing in her father Rev. C.L. Franklin’s Detroit church choir after her mother’s early death, to finding chart success as she became a powerful voice for civil rights, to performing at three presidential inaugurations. The book includes chapters on Franklin’s Amazing Grace, the best-selling gospel album of all time; her collaborations with Whitney Houston, George Michael, Lauryn Hill, and more; and the special connection she shared with President Barack Obama. Plus: a behind-the-scenes peek at the Aretha biopic, Respect, and an interview with its star, Oscar-winner Jennifer Hudson.